Multipoint MultimediaSynchronization: A Petri Net Based Approach - Dutta, Animesh; Pal, Koninika; Dasgupta, Ranjan; Bhattacharya, Swapan (INFOCOMP Journal of Computer Science, 2012)
Maintaining the satisfactory QoS, synchronization is a big challenge to the researcher in the field of Information and Communication Technology (ICT). In this paper we address a multimedia synchronization issue called multipoint synchronization which is necessary in some distributed collaborative application like teleteaching, teleconferencing etc.,involving the play out process of same media stream at different receivers at the same time to achieve fairness among the receivers. We found the in capability of existing petri net to model the above synchronization issue. Some new features are added in existing petri nets to increase its modeling and analyzing power, called self modifying stochastic color petri net (SMSCPN).Then the synchronization issue is modeled with the help of SMSCPN and an generalized algorithm is proposed to achieving multipoint synchronization in IP network. Also some metrics are defined that can measurethe performance of the proposed synchronization algorithm.